2023
DOI: 10.1021/jacs.3c04978
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Arsenic Secondary Metabolism in Actinomycetes from the Structure and Biosynthesis of Bisenarsan

Abstract: The unique bioactivities of arsenic-containing secondary metabolites have been revealed recently, but studies on arsenic secondary metabolism in microorganisms have been extremely limited. Here, we focused on the organoarsenic metabolite with an unknown chemical structure, named bisenarsan, produced by well-studied model actinomycetes and elucidated its structure by combining feeding of the putative biosynthetic precursor (2-hydroxyethyl)­arsonic acid to Streptomyces lividans 1326 and detailed NMR analyses. Bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Feeding studies and NMR analysis have revealed the chemical structure of the organoarsenic metabolite, bisenarsan 29 , from the actinomycete, Streptomyces lividans 1326. 28 Identification of the bisenarsan gene cluster revealed that the C–As bond is formed by the cofactor-independent phosphoglycerate mutase homologue, BsnN via an intramolecular rearrangement of arsenoenolpyruvate.…”
mentioning
confidence: 99%
“…Feeding studies and NMR analysis have revealed the chemical structure of the organoarsenic metabolite, bisenarsan 29 , from the actinomycete, Streptomyces lividans 1326. 28 Identification of the bisenarsan gene cluster revealed that the C–As bond is formed by the cofactor-independent phosphoglycerate mutase homologue, BsnN via an intramolecular rearrangement of arsenoenolpyruvate.…”
mentioning
confidence: 99%